PREVALENCE OF CARDIORENAL SYNDROME IN PATIENTS ADMITTED FOR ACUTE DECOMPENSATED HEART FAILURE AND ITS CORRELATION WITH IN-HOSPITAL OUTCOMES - Yaqoob, Naveed; Khalid, Fahad; Khan, Muhammad Fareed; Anwar, Wahab; Khan, Muhammad Fasihullah; Iqbal, Muhammad Hasnain (Journal of Ayub Medical College Abbottabad, 2024)
Background: Cardiorenal syndrome is the prevalent form of the syndrome in Pakistan. Despite the rising importance of CRS, more information is needed to understand comorbidities and hospital outcomes. This research study explores the prevalence, and In-hospital outcomes of patients admitted for Acute Decompensated Heart Failure at the tertiary care hospital of Islamabad at the age of above 18. Methods: This cohort study was conducted at the tertiary care hospital in Islamabad from January 2024 to June 2024. Data were collected from 200 known ADHF patients who visited the CCU (OPD) and ward through a structured questionnaire. The data were analyzed using SPSS version 25. Result: The majority of the sample was diagnosed with Type 1 Cardiorenal Syndrome, which accounted for 30% of the total. Cardiorenal Syndrome Types 3 and 5 had a prevalence of 20% each among the patients, while Types 2 and 4 had a prevalence of 15% each. This suggests that Type 1 was more prevalent, but the other types were equally distributed. The mortality rate in the Hospital was highest for Type 5 CRS at 15% and Type 3 CRS at 13%. During this period, Type 2 CRS exhibited the lowest mortality rate. Type 3 CRS had the most extended average hospitalization duration. Conclusion: It was concluded in our study that cardiorenal syndrome is the prevalent form among admitted patients with ADHF, and the government needs to increase awareness about health and health-related risk factors related to the communities.